1990
DOI: 10.1007/bf02411549
|View full text |Cite
|
Sign up to set email alerts
|

A differential molecualr topography of the Pr and Pfr forms of native oat phytochrome as probed by fluoresence quenching

Abstract: Tryptophan (Trp) surface topography of the red- and far-red-absorbing forms of phytochrome (Pr, Pfr) ofAvena sativa L. has been investigated by analyzing quenching of the two components of Trp fluorescence decay, in order to understand the differences in the two forms at the molecular level. Stern-Volmer kinetic analysis of the quenching data for two cationic surface quenchers, Cs(+) and Tl(+), showed strong quenching of the short component of the Pr fluorescence (Stern-Volmer constants,K sv , 27.2 and 21.4 M(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Trp570 in oat phytochrome, which corresponds to Trp567 in pea phytochrome, was supposed to be responsible for the quenching of Trp fluorescence by cationic ions in Pfr (Singh & Song, 1990). All these results indicate that conformational changes occur in the hinge region on phototransformation, which suggests the involvement of Trp567 in the hydrophobicity increase based on the same reason described above.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Trp570 in oat phytochrome, which corresponds to Trp567 in pea phytochrome, was supposed to be responsible for the quenching of Trp fluorescence by cationic ions in Pfr (Singh & Song, 1990). All these results indicate that conformational changes occur in the hinge region on phototransformation, which suggests the involvement of Trp567 in the hydrophobicity increase based on the same reason described above.…”
Section: Discussionsupporting
confidence: 53%
“…The larger UV RR spectral change in small phytochrome, which lacks the three Trp's, again supports the idea that the Trp residues involved in the hydrophobicity increase are located in the chromophoric domain. However, this does not exclude the possibility of subtle alteration in the surface topography of Trp773 and Trp777 during the phototransformation as reported from their fluorescence quenching studies (Singh & Song, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…Although complicated by the number of Trp residues, dynamic quenching studies used on Avena phytochrome showed there are substantial alterations in the molecular and electrostatic microenvironments of the fluorescent tryptophans (Singh et al, 1988). Singh and Song (1990) resolved the fluorescence decays of these indole-containing residues into two lifetime components. Quenching behavior demonstrated each component, short and long, represented a separate group of Trp residues which are differentially exposed in Pr and Pfr.…”
mentioning
confidence: 99%
“…3; Nakazawa and Manabe 1993). Physicochemical differences between the protein moieties of phytochrome, as determined by uv absorption spectroscopy, uv circular dichroism (Singh et al 1989, Vierstra et al 1987, uv Raman spectroscopy (Toyama et al 1993, Mizutani et al 1993, infrared absorption (Siebert et al 1990, Foerstendorf et al 1996, and quenching of Trp fluorescence (Singh et al 1989, Singh and Song 1990, Wells et al 1994, have also been reported. Such studies have revealed conformational changes in phytochrome during the phototransformation, and some of the changes were identified as changes in the non-chromophoric carboxy-terminal domain.…”
mentioning
confidence: 98%